Electrospun Polyvinylpyrrolidone-Gelatin and Cellulose Acetate Bi-Layer Scaffold Loaded with Gentamicin as Possible Wound Dressing - López Calderón, Héctor Daniel; Avilés Arnaut, Hamlet; Galán Wong, Luis Jesús; Almaguer Cantú, Verónica; Laguna Camacho, J. R.; Calderón Ramón, C.; Escalante Martínez, J. E.; Arévalo Niño, Katiushka (Molecular Diversity Preservation International, 2020)
Acceleration of wound healing can be achieved with the use of wound dressings. Through the electrospinning technique, a polymeric scaffold composed of two layers was processed: a gelatin and polyvinylpyrrolidone layer with gentamicin, and a second layer of cellulose acetate. The conditions for the electrospinning process were standardized for voltage parameters, feed flow and the distance from the injector to the collector. Once the values of the main variables for the electrospinning were optimized, a three-hour processing time was established to allow the separation of the material from the collector. The obtained material was characterized by observations on scanning electron microscopy, Fourier transform infrared spectroscopy and thermal analysis; contact angle measurement was performed to evaluate wettability properties, and antibacterial activity against Pseudomonas aeruginosa and Staphylococcus aureus were evaluated using the Kirby–Bauer test. The obtained fibers that form the bi-layer scaffold present diameters from 100 to 300 nm. The scaffold presents chemical composition, thermal stability, wettability characteristics and antibacterial activity that fulfill the proposal from this study, based on obtaining a scaffold that could be used as a drug delivery vehicle and a wound dressing material.